Resilient heritage language maintenance: the interplay of family, culture, and pragmatic choices - Bilgory-Fazakas, Orsolya; Armon-Lotem, Sharon (Frontiers in Psychology, 2025)
IntroductionGlobalization and transnational mobility have contributed to linguistic and cultural diversity. Yet small migrant communities trying to preserve their heritage language (HL) face challenges. This study investigates the intersection of family language policies (FLPs), migration, and multilingualism within the Hungarian-speaking immigrant community in Israel, focusing on the social and affective dimensions of HL transmission. Grounded in the FLP framework, it explores how cultural heritage, parental attitudes, and pragmatic considerations shape HL transmission and maintenance, particularly within transnational families, where maintaining ties with extended family often serves as a key motivation.MethodsThe study involved 51 Hungarian-speaking adults who immigrated to Israel post-2000, with at least one child under 18. Participants were functional multilinguals who used Hungarian (HL), Hebrew (societal language, SL), and English daily. An online questionnaire assessed participants’ biographical information, language use, attitudes toward HL maintenance, and code-switching. Self-rated language fluency was measured using the CEFR scale, and data were analysed using Principal Component Analysis (PCA) and multilinear regression to identify predictors of HL transmission and maintenance. Thematic analyses (TA) were used to identify and report themes within the qualitative data.ResultsFindings revealed that most families adopted bilingual FLPs, balancing HL and societal language (SL) use. PCA identified two significant components: cultural heritage (including parental emphasis on HL literacy, cultural practices, and linguistic immersion) and communication in HL (focused on child-directed HL use). Parental attitudes towards code-switching negatively correlated with HL use, while efforts to transmit cultural heritage positively predicted successful HL maintenance. Multilinear regression analysis identified cultural heritage transmission and attitudes toward code-switching as significant predictors of HL maintenance. Grandparents played a central role in encouraging HL transmission and maintenance, with strong correlations observed between parental efforts and children’s ability to communicate with extended family.ConclusionThis study examines how Hungarian-speaking immigrant families in Israel, a small and underrepresented community, maintain their HL. The findings suggest that balanced exposure to both HL and the SL supports HL sustainability, with intergenerational ties playing a key role. However, the study’s scope is limited to highly educated, mid-high SES families, so results may not apply to the entire community.